Comparison of Modified Stoppa Approach versus Ilioinguinal Approach for Anterior Acetabular Fractures : Modified Stoppa Approach versus Ilioinguinal Approach - Sajid, Muhammad; Raza, Javed Hassan; Gill, Usman Nazir; Sohail, Muhammad Amir; Khan, Junaid; Qasim, Mohammad (Pakistan Journal of Health Sciences, 2023)
Achieving an anatomically precise reduction of acetabular fractures is vital for obtaining the best possible outcome. The Modified Stoppa approach has demonstrated advantages such as reduced blood loss and shorter surgical durations when dealing with anterior acetabular fractures in comparison to the ilioinguinal approach. Objective: To evaluate the outcomes of the modified Stoppa approach in comparison to the ilioinguinal approach. Methods: The quasi-experimental study was conducted within the Department of Orthopaedic Surgery at Jinnah Hospital during the period from November 12, 2018, to May 11, 2019.The study involved 60 patients, with 30 individuals in each group. Group A underwent treatment for anterior acetabular fractures using the modified Stoppa method, while Group B received treatment using the ilioinguinal approach. Results: Patients ranged between 16-60 years of age with mean age of 36.9±11.2 in group-A and 35.6±10.3 year in group-B. Majority of the patients were male in both groups. Left anatomical side was involved in most of the patients in both groups. The mean duration of injury in group-A was 7.07±2.6, while in group-B, it was 6.6±2.4. A statistical analysis revealed a significant difference between the two groups in terms of mean operative time and blood loss (p<0.001). Furthermore, stratification was performed based on age, gender, and the duration of injury, and significant differences were observed in these stratified subgroups as well. Conclusions: Our findings showed that modified Stoppa technique outperforms the ilioinguinal method by exhibiting reduced blood loss and shorter operative durations. This positions the modified Stoppa technique as a superior option for addressing anterior acetabular fractures.